Improving Listening Skill of The Seventh Grade Students Using Games at MTsN Mojokerto - Hanna Andyani (Language Center of Islamic Institute of Uluwiyah, Mojokerto, Indonesia., 2016)
Based on the study conducted on research at MTsN Mojokerto, the researcher found that there are some problems with teaching English especially for listening of seventh grade students at MTsN Mojokerto, those are: 1) most of the students’ scores on listening test are still under the minimum of standard score (KKM) of 79; 2) most students are not attracted to follow the listening activities; 3) students are difficult to understand the native speech in a tape recorder.The main purpose of the study is to improve listening skill of seventh grade students using games. Research design for this study was Classroom Action Research and the researcher used listening tests and observation checklists as instruments.The criteria of success was successfully achieved in Cycle 2 with the percentage of 74%